Developing E-learning Based MOODLE in Learning Ecosystem to Improve Environmental Literacy in Class X Enrichment Program - Haske, Anita Sugiansih; Wulan, Ana Ratna (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
The purpose of this study was to produce e-learning based moodle that can improve environmental literacy class X and can streamline enrichment program. This study was a quasi-experimental, with a study population of class X of SMAN 3 Sumedang 2014/2015 school year. The study sample consisted of two classes include experimental class and control class. The study sample taken are students who have passed KKM material ecosystem from daily test results by teachers so that they can follow the activities of enrichment program in the learning ecosystem to gain a broad knowledge. The experimental class in this study, students attend enrichment program through e-learning based moodle so that they can access information about environmental issues related to the ecosystem as much as possible, whenever and wherever. While, the control class students attend enrichment program accordance with enrichment program usually done by teachers of subjects in SMAN 3 Sumedang, through discussions and solving environmental problems. The sampling technique using random class methods. The research design in this study is the matching- only pretest-posttest control group design. Data collection instrument is a test environment literacy (Ecological knowledge, verbal commitment intention to act, environmental sensitivity, cognitive skill, and actual commitment pro environmental behaviour). Data analisis using a independent sample t-test. Based on the results of data analysis, it was found that environmental literacy domain ecological knowledge there were not significant differences between the experimental class and control class (Sig=0,082, p>0,05), environmental literacy domain disposition sub domain verbal commitment intention to act there were significant differences between the experimental class and control class (Sig=0,003, p<0,05), environmental literacy domain disposition sub domain environmental sensitivity there were significant differences between the experimental class and control class (Sig=0,001, p<0,05), environmental literacy domain cognitive skill there were significant differences between the experimental class and control class (Sig=0,003, p<0,05), and environmental literacy domain actual commitment pro environmental behaviour there were significant differences between the experimental class and control class (Sig=0,034, p<0,05).Key words : E-learning, Moodle, Ecosystem, Environmental literacy, Enrichment program